Glutamyl-Prolyl-tRNA Synthetase Regulates Epithelial Expression of Mesenchymal Markers and Extracellular Matrix Proteins: Implications for Idiopathic Pulmonary Fibrosis - Song, Dae-Geun; Kim, Doyeun; Jung, Jae Woo; Nam, Seo Hee; Kim, Ji Eon; Kim, Hye-Jin; Kim, Jong Hyun; Pan, Cheol-Ho; Kim, Sunghoon; Lee, Jung Weon (Frontiers in Pharmacology, 2018)
Idiopathic pulmonary fibrosis (IPF), a chronic disease of unknown cause, is characterized by abnormal accumulation of extracellular matrix (ECM) in fibrotic foci in the lung. Previous studies have shown that the transforming growth factor b1 (TGFβ1) and signal transducers and activators of transcription (STAT) pathways play roles in IPF pathogenesis. Glutamyl-prolyl-tRNA-synthetase (EPRS) has been identified as a target for anti-fibrosis therapy, but the link between EPRS and TGFβ1-mediated IPF pathogenesis remains unknown. Here, we studied the role of EPRS in the development of fibrotic phenotypes in A549 alveolar epithelial cells and bleomycin-treated animal models. We found that EPRS knockdown inhibited the TGFβ1-mediated upregulation of fibronectin and collagen I and the mesenchymal proteins α-smooth muscle actin (α-SMA) and snail 1. TGFβ1-mediated transcription of collagen I-α1 and laminin γ2 in A549 cells was also down-regulated by EPRS suppression, indicating that EPRS is required for ECM protein transcriptions. Activation of STAT signaling in TGFβ1-induced ECM expression was dependent on EPRS. TGFβ1 treatment resulted in EPRS-dependent in vitro formation of a multi-protein complex consisting of the TGFβ1 receptor, EPRS, Janus tyrosine kinases (JAKs), and STATs. In vivo lung tissue from bleomycin-treated mice showed EPRS-dependent STAT6 phosphorylation and ECM production. Our results suggest that epithelial EPRS regulates the expression of mesenchymal markers and ECM proteins via the TGFβ1/STAT signaling pathway. Therefore, epithelial EPRS can be used as a potential target to develop anti-IPF treatments.